Different Drugs, Same End: Ultrastructural Hallmarks of Autophagy in Pathogenic Protozoa - Pedra-Rezende, Yasmin; Macedo, Isabela S.; Midlej, Victor; Mariante, Rafael M.; Menna-Barreto, Rubem F. S. (Frontiers in Microbiology, 2022)
Protozoan parasites interact with a wide variety of organisms ranging from bacteria to humans, representing one of the most common causes of parasitic diseases and an important public health problem affecting hundreds of millions of people worldwide. The current treatment for these parasitic diseases remains unsatisfactory and, in some cases, very limited. Treatment limitations together with the increased resistance of the pathogens represent a challenge for the improvement of the patient´s quality of life. The continuous search for alternative preclinical drugs is mandatory, but the mechanisms of action of several of these compounds has not been described. Electron microscopy is a powerful tool for the identification of drug targets in almost all cellular models. Interestingly, ultrastructural analysis showed that several classes of antiparasitic compounds induced similar autophagic phenotypes in trypanosomatids, trichomonadids, and apicomplexan parasites as well as in Giardia intestinalis and Entamoeba spp. with the presence of an increased number of autophagosomes as well as remarkable endoplasmic reticulum profiles surrounding different organelles. Autophagy is a physiological process of eukaryotes that maintains homeostasis by the self-digestion of nonfunctional organelles and/or macromolecules, limiting redundant and damaged cellular components. Here, we focus on protozoan autophagy to subvert drug effects, discussing its importance for successful chemotherapy.